Akad Jual Beli yang Dilarang Prespektif Hukum Islam - Harisman Harisman; M.Yadhi Harahap (DOKTRINA: JOURNAL OF LAW, 2023)
This study discusses buying and selling contracts which are prohibited from the perspective of Islamic law. Basically, Islam itself allows buying and selling anything as long as it does not conflict with Shari'a law. But in reality, in practice there are still many buying and selling that are prohibited from being carried out. Normative research was carried out by searching the verses of the Qur'an, hadith and literature that are related to this discussion. The results of the search are analyzed qualitatively and are described with the aim of obtaining an explanation as intended in the discussion. Based on the study, it was found that several types of sale and purchase agreements were prohibited, including: 1) Selling and buying khamr, carrion, pigs and statues, 2) Selling and buying under subterfuge, 3) Selling and buying Gharar, 4) Selling and buying Najsy, and 5) Selling Buy usury.